THE STATE AND PROSPECTS OF MARKETING STRATEGIES FOR SMALL AND MEDIUM BUSINESS ENTERPRISES IN UKRAINE - Oleksandr Teletov; Vladimir Grigorenko (Сучасний стан наукових досліджень та технологій в промисловості, 2019)
The subject of research is the transform processes taking place at Ukrainian small and medium enterprises and development of theirs marketing strategies. The purpose of the work is to study the role of marketing strategies for small and medium enterprises in Ukraine. The article solves the following tasks: analysis of small and medium enterprises functioning in Ukraine; determining the functioning differences between their marketing management and the marketing management of large industrial enterprises; a description of the marketing strategies developed by the small and medium enterprises. Methods of mathematical statistics, theoretical generalization, marketing researches have been used. The following results were obtained: The general situation at the small businesses in Ukraine was analyzed. The state of small and medium business enterprises in the conditions of creation of united communities and their possible entry into territorial clusters as a tool for increasing the competitiveness of some economic entities of the region was considered. The organization differences between marketing management at large industrial enterprises and small businesses were given. Since international partners have repeatedly pointed out the lack of modern economic education at the small and medium enterprises management, the directions for its possible receipt were presented. It was shown that since the concept of marketing in a market economy is the basis of successful entrepreneurial activity, it became required to develop a theoretical and methodological base at the state level in order to take into account the features of small and medium businesses and coordinating the related actions. The ways of developing small and medium enterprises marketing strategies are given. Conclusions. The necessity to increase the innovative potential of small and medium enterprises in Ukraine in the conditions of administrative reform; development of entrepreneurial skills in the persons engaged in this process and development of marketing strategies of the corresponding enterprises has been confirmed.